A regulamentação do procedimento de formação do preço de referência das licitações públicas : um estudo de caso no MPF/ES nos anos de 2013 a 2017 - Queiroz, Wayata Arrivabene de Freitas (2018)
The brasilian State rules itself by na intrincated amount of norms destinated to ensure to tis citizens the goods and services essencials to life and human dignity. To that, subject itself to procedures e prescriptions established in the law, being of great relevance the pricing of the goods and services bidded, wich is denominated in the bidding procedures by reference price. Once was the understanding of the Public Administration and still is for many public agencies that the reference price of the governamental biddings is the smallest value obtained through market inquiry. However, frequently the Public Administration faces problems coming from inadequacy of the reference price towards the prices effectively praticated by the market, causing elevated percentages of desertions and failures in public biddings. Attentive to this fact, the Federal Public Ministry in the State of Espírito Santo (MPF/ES) edited the Service Instruction nº 05, of 17 August 2015, regulamentating the procedure in wich is obtained the reference price, that started to count with parameters of gathering the prices of the market and with the use of the arithmetic mean and median upon the obtained prices. Meanwhile, the pratical results of this new method of composition of the reference price are unknown. Because of that was accomplished a case study with qualitative nature and usage of comparative method, aiming to study the Service Instruction and to known the results coming in terms of effectiviness and economicity of the public biddings done by the MPF/ES. To that was extracted information related to the adjudication, failure and desertion of the bidings done by the MPF/ES between the years 2013 and 2017, as well the prices obtained in the market inquiry, reference prices e adjudication prices. The results of the research reveals advantages and disadvantages from the regulamentation of the procedure of formation of the reference price, unknown by many public agencies, including the MPF/ES, alowing the comparison with the previous methodology. It is about a technic of analysis developed em in real situation tha might serve as a model to be used by other institutions that are subject to the same rules of public bidding